2017
DOI: 10.1007/s40072-017-0107-4
|View full text |Cite
|
Sign up to set email alerts
|

Weak universality of dynamical $$\Phi ^4_3$$ Φ 3 4 : non-Gaussian noise

Abstract: We consider a class of continuous phase coexistence models in three spatial dimensions. The fluctuations are driven by symmetric stationary random fields with sufficient integrability and mixing conditions, but not necessarily Gaussian. We show that, in the weakly nonlinear regime, if the external potential is a symmetric polynomial and a certain average of it exhibits pitchfork bifurcation, then these models all rescale to 4 3 near their critical point.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 27 publications
0
15
0
Order By: Relevance
“…Similar results in higher dimensions d = 2, 3 were conjectured in [GLP99] but a complete proof in the two dimensional case was given only recently [MW16]. A similar convergence result is expected to hold in three dimensions, though a complete proof has not been established yet; however in [HX16,SX16] it was shown that a class of continuous phase coexistence models rescale to Φ 4 3 . 1 The tunable parameter in all of the results on convergence of variants of the asymmetric simple exclusion process to KPZ, is the asymmetry of the exclusion process: making it smaller and smaller corresponds to making the model locally more "Gaussian" which in turn corresponds to the fact that the dynamics on small scales are dominated by solutions of the linear equation.…”
Section: Introductionmentioning
confidence: 56%
“…Similar results in higher dimensions d = 2, 3 were conjectured in [GLP99] but a complete proof in the two dimensional case was given only recently [MW16]. A similar convergence result is expected to hold in three dimensions, though a complete proof has not been established yet; however in [HX16,SX16] it was shown that a class of continuous phase coexistence models rescale to Φ 4 3 . 1 The tunable parameter in all of the results on convergence of variants of the asymmetric simple exclusion process to KPZ, is the asymmetry of the exclusion process: making it smaller and smaller corresponds to making the model locally more "Gaussian" which in turn corresponds to the fact that the dynamics on small scales are dominated by solutions of the linear equation.…”
Section: Introductionmentioning
confidence: 56%
“…Moreover our construction is not restricted to the Gaussian setting and applies to any choice of the driving noise with minimal integrability conditions. In particular this allows to recover all the renormalisation procedures used so far in applications of the theory [32,[38][39][40]42,51]. It reaches however far beyond this and shows that the BPHZ renormalisation procedure belongs to the renormalisation group of the regularity structure associated to any class of subcritical semilinear stochastic PDEs.…”
Section: Mathematics Subject Classification 16t05 • 82c28 • 60h15 1 Imentioning
confidence: 76%
“…Using the machinery developed there Hairer and Wu [11] proved a weak universality result for three dimensional reaction-diffusion equations in the case of Gaussian noise and a polynomial non-linearity, within the context of regularity structures. Weak universality for reaction-diffusion equations driven by non Gaussian noise is analysed in Shen and Wu [22]. Recently, important results concerning the stochastic quantisation equation we obtained by Mourrat and Weber.…”
Section: Theorem 11 (Convergence Of the Solution)mentioning
confidence: 99%